2015
DOI: 10.1177/2040622315587256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air quality on lung health: myth or reality?

Abstract: Abstract:The respiratory system is a primary target of the harmful effects of key air pollutants of health concern. Several air pollutants have been implicated including particulate matter (PM), ozone (O 3 ), nitrogen dioxide (NO 2 ) polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs). It is well known that episodes of exposure to high concentrations of outdoor air pollutants can cause acute respiratory exacerbations. However, there is now increasing evidence suggesting that significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 68 publications
1
38
0
1
Order By: Relevance
“…Pittsburgh, Pennsylvania, is characterized by a complex terrain of hills and river valleys, episodic traffic congestion, and a few large remaining steel mills (Edgar Thomson Steel Works) and coke plants (Clairton Coke Works) located southeast of Pittsburgh, all contributing to locoregional variability in pollutant concentrations, including PM 2.5 and BC . The pulmonary effects of air pollutant exposure have been studied in more detail, demonstrating an association between PM exposure and lower airway diseases, including asthma and COPD . Exposure to PM 2.5 has been shown to affect lung development and function, leading to an increased risk of developing asthma and disease exacerbations later in life .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pittsburgh, Pennsylvania, is characterized by a complex terrain of hills and river valleys, episodic traffic congestion, and a few large remaining steel mills (Edgar Thomson Steel Works) and coke plants (Clairton Coke Works) located southeast of Pittsburgh, all contributing to locoregional variability in pollutant concentrations, including PM 2.5 and BC . The pulmonary effects of air pollutant exposure have been studied in more detail, demonstrating an association between PM exposure and lower airway diseases, including asthma and COPD . Exposure to PM 2.5 has been shown to affect lung development and function, leading to an increased risk of developing asthma and disease exacerbations later in life .…”
Section: Discussionmentioning
confidence: 99%
“…19 The pulmonary effects of air pollutant exposure have been studied in more detail, demonstrating an association between PM exposure and lower airway diseases, including asthma and COPD. [5][6][7] Exposure to PM 2.5 has been shown to affect lung development and function, leading to an increased risk of developing asthma and disease exacerbations later in life. 21 Mady et al showed that PM 2.5 was significantly associated with incidence of FESS with a 1.89-fold increased risk in need for FESS in the CRSsNP population with each unit increase in PM 2.5 (p = 0.015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PM2.5 is associated with acute and long-term health impacts to the cardiovascular and respiratory systems and is linked to an increase in hospital visits, lung cancer, asthma, chronic bronchitis, chronic obstructive pulmonary disease (COPD), dysrhythmia, low birth weight, and pre-term birth (DeFranco et al 2016;Stieb et al 2016;Marino et al 2015;Raaschou-Nielsen et al 2013;Dominici et al 2006;Nel 2005;EPA 2003). Exposure is especially harmful to children, the elderly, and individuals with existing respiratory or cardiovascular conditions (Brown et al 2014;WHO 2013).…”
Section: Particulate Matter and Ungdmentioning
confidence: 99%